2018
DOI: 10.5858/arpa.2018-0020-ra
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathologic Diagnosis of Epithelioid and Mixed-Type Malignant Mesothelioma: Ten Years of Clinical Experience in Relation to International Guidelines

Abstract: - A conclusive diagnosis of MM can be obtained based on the criteria defined by the guidelines with high positive predictive value. When diagnosed in this way, subsequent therapy should be initiated without further delay. With the earlier diagnosis obtained by cytology, a better effect of chemotherapy can be expected, as shown by the longer overall survival in these patients compared with those with a histopathologic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
(48 reference statements)
2
34
0
1
Order By: Relevance
“…Biphasic tumors often comprise elements of both epithelioid and sarcomatoid tumors (2). The mesothelial markers discussed as above applies to this subtype as well (23).…”
Section: Differentiating Mesothelioma From Metastatic Carcinomasmentioning
confidence: 99%
“…Biphasic tumors often comprise elements of both epithelioid and sarcomatoid tumors (2). The mesothelial markers discussed as above applies to this subtype as well (23).…”
Section: Differentiating Mesothelioma From Metastatic Carcinomasmentioning
confidence: 99%
“…There is scant reference to histology with only fleeting reference to core biopsy and no discussion of video assisted thoracic surgery (VATS) or other surgical techniques for diagnosis of mesothelioma (these may be considered beyond the scope of the guidelines' subject matter). What also fails to be acknowledged is that major thoracic (or abdominal) surgery for mesothelioma ought to require a definitive diagnosis by whatever means before it can be considered appropriate, even though it is suggested that early diagnosis by Cytology (especially early presentation with the first effusion) can lead to a better chemotherapy effect and longer overall survival that those with a histopathologic diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous dual/multiple immunostains by using peroxidase and alkaline phosphatase methods together (different chromogens) are found to be very useful in effusion cytology. Combined use of BerEp4/Calretinin, or desmin/EMA, or WT1/AE1‐AE3 are giving reliable results in different contexts, such as desmin/EMA for distinguishing malignant from reactive mesothelial proliferations; or WT1/AE1‐AE3 for grouping malignant effusions into discrete subsets narrowing the differential diagnosis . Dual staining can be applied both to cytological slides (cytospins, LBC) and cell block sections.…”
Section: Managementmentioning
confidence: 99%